Pengaruh Masa Kerja dan Shift Kerja Terhadap Kelelahan Kerja pada Perawat Inap di Rumah Sakit PKU Muhammadiyah Surakarta - Pramitasari, Riska Meila; , Sri Darnoto, SKM.,M.PH (2016)
Work of a nurse in giving treatment service was not quit of arrangement of office hours in a hospital which more knowledgeable with the term of work shift. This fatigue lead into the psychological function reduction and physiology able to be eliminated with the cure effort. PKU Muhammadiyah Hospital apply the system shift used consisted of 4 group shift where every group arranged 3 day work the morning shift continued 3 day work the night shift, take a rest 2 day hereinafter work the noon shift 3 day and take a rest 1 day. The result survey to 17 nurses known that emerging fatigue sigh at nurse like existence of headache symptom after shift night, concentration degradation, often condense, tired and sleepy from head to foot. Purpose of this research was to know the influence of work period and work shift to fatigue work at nurse stay with the pain of PKU Muhammadiyah Surakarta Hospital. This research type was using analytic survey with cross sectiopnal approach. Sampel Research taken in Kuota Sampling so that obtained sample counted 52 nurses. The data analyse was using chi square test. Result of analysis known that majority of woman gender nurses (53,8%), 23-30 years old ( 50%), have maried (76,9%), having education D3 nurse (75%). Seen from period working majority nurses have the old period working (46,2%) with the majority nurses reside at night shift ( 50%) and have the middle fatigue work (53,8%). From bivariat analyse result can be conclusion that there were influence significant between period working and work fatigue of nurses (p = 0,000 <0,05) and there were influence significant between working shift and work fatigue of nurses (p = 0,000 <0,05)